2017
DOI: 10.22336/rjo.2017.47
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical results and complications after silicone oil removal

Abstract: The aim of the report was to evaluate anatomical results and intra and postoperative complications after silicone oil (SIO) removal.Methods: Retrospective, interventional study evaluating consecutive cases with ambulatory SIO removal after vitrectomy for complex retinal detachments. The anatomical result was the main followed parameter. Intra and postoperative complications and also intraocular pressure changes were evaluated. Cases were followed-up for at least 12 months. Results: A total of 98 consecutive ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…In a recent macula-on retinal detachment study, higher IOP during SO endotamponade was the biggest risk factor for vision loss significantly different at pre- and post SO removal ( p = 0.08). This result is similar to the study by Brănişteanu et al (2017), who reported a decrease in IOP post SO removal [ 32 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In a recent macula-on retinal detachment study, higher IOP during SO endotamponade was the biggest risk factor for vision loss significantly different at pre- and post SO removal ( p = 0.08). This result is similar to the study by Brănişteanu et al (2017), who reported a decrease in IOP post SO removal [ 32 ].…”
Section: Discussionsupporting
confidence: 92%
“…Several reports also showed that the first sign of SO emulsification can be found within the first 3 months post-operatively, or even 4 weeks after endotamponade. Due to a large number of cases of SO emulsification within 1 year, the consensus recommended that removal must be carried out within this time interval [ 32 , 33 ]. The mean IOP for all age groups and durations of SO application did not affect pre removal measurements or follow up.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective evaluation of 98 consecutive cases with complex retinal detachments that underwent 23G vitrectomy and high viscosity SIO endotamponade (Oxane ® 5700) we noted significant IOP changes during both SIO endotamponade and after SIO removal ( 8 ). In 52 out of 98 cases (53.06%) with no preexisting glaucoma, IOP increased over 21 mmHg requiring topical antiglaucomatous medication during endotamponade.…”
Section: Current State Of Knowledge Regarding Intraocular Pres- Sumentioning
confidence: 95%
“…Many complications have been associated with SIO endotamponade. While refractive change is a perturbing yet harmless feature during endotamponade, more severe complications may occur as macular pucker, cystoid macular edema, and rubeosis iridis ( 8 ). Long-standing SIO endotamponade is associated with significant ocular complications such as cataract formation, corneal decompensation, band keratopathy, and orbital leakage ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…The two groups differed significantly in the incidence of complications (χ 2 =4.2787, P=0.0386). None of the affected eyes were complicated with transient intraocular hypotension (7), vitreous hemorrhage or endophthalmitis.…”
Section: Resultsmentioning
confidence: 99%